3D finite element modeling of directional hydraulic fracturing based on deformation reinforcement theory. (February 2018) - Deng, Jianqiang; Yang, Qiang; Liu, Yaoru; Liu, Yi; Zhang, Guoxin
Abstract: The effective stress principle of Biot's consolidation theory is first introduced into deformation reinforcement theory to model directional hydraulic fracturing. The unbalanced force considering the effective stress of fluid is derived and a more effective vector type criterion of hydraulic fracture initiation and propagation is proposed. The unbalanced force magnitude indicates the fracture degree and direction clearly indicates the fracture propagation direction. The new theory and method is first implemented into 3D finite element and the numerical modeling is verified by true tri-axial experiments. The investigation results indicate that unbalanced force can track and locate the hydraulic fracture propagation well.